Addition of glycerol to agroindustrial residues of bioethanol for fuel-flexible agropellets: Fundamental fuel properties, combustion, and potential slagging and fouling from residual ash - da Silva Viana, Ronaldo [UNESP]; May, André; Moreira, Bruno Rafael de Almeida [UNESP]; Cruz, Victor Hugo [UNESP]; Junior, Nilson Aparecido Vieira; Moura da Silva, Evandro Henrique Figueiredo; Simeone, Maria Lucia Ferreira (Elsevier, 2023)
Glycerol is a by-product of biodiesel. It offers a suitable additive in fabricating fuel-grade solids. However, studies on biomass-glycerol frameworks for energy generation are still emerging topics, driving the need to conduct further experiments and trials to develop alternatives (e.g., non-wood pellets and co-pelleting lines) and understand relationships between raw materials, products, and processes. We, therefore, analyzed whether adding glycerol to agroindustrial residues of bioethanol, namely sugarcane bagasse (first-generation) and lignocellulosic cake (second-generation), could develop suitable agropellets for heating and power. We combined sugarcane bagasse and lignocellulosic cake at 100/0, 75/25, 50/50, 25/75, and 0/100 (wt%, dry basis) for single and hybrid solid biofuels. We mixed them with glycerol at 0, 1, 2, and 3 wt% for a controllable addition and then pelletized them on an automatic press at 200 MPa and 150 °C. We assessed the models for glycerol-containing agropellet for standard fuel properties, such as water, volatile matter, fixed carbon, bulk density, and calorific value. In addition, we conducted thermogravimetry and energy-dispersive x-ray spectroscopy to provide further information about their thermal stability and decomposition, external morphology, and propensity to slagging and fouling. We obtained evidence for sugarcane bagasse and lignocellulosic cake developing high-quality pellets. Their products could be as dense (1161.5–1277.3 kg m−3) and energetic (20.30–21.75 MJ kg−1) as premium-grade wood biofuels; hence, they can offer stakeholders excellent solutions to address high-throughput pelleting lines and generate heat and power in the strictest residential and commercial combustion systems. Blending these materials at 25/75 (wt%, dry basis) could develop a lower degree of compactness of 1135.55 kg m−3. However, introducing glycerol up to 2%wt to such a mixture could increase it to 1162 kg m−3 while maintaining its calorific feature. As a result, it enhanced energy density from 24.1 to 27 GJ m−3. At 3 wt%, however, such an additive can limit technical performance because of its lubricating feature. In addition, it can increase the degree of roughness on the surface, making it easier for samples to reabsorb isothermally available water from the surroundings, implicating low-grade fuels. Furthermore, it can reduce heat transport while increasing physical deposits (i.e., foul and slag) during combustion, as it contained 2.9% inorganic salts. However, its impurities cannot be a limiting factor to the utilization of agropellets in boilers since they only generated 1.3% residue. Therefore, we advanced the field's prominence in adding glycerol to non-woody materials for pelletization and co-densification as a relatively new topic. Stakeholders may benefit from our products to address high-throughput energy-producing systems while valorizing waste.
Keywords: Blend; Pelletization; Solid biofuel; Sugarcane bagasse